30 EVOLOCUMAB USE IN CLINICAL PRACTICE IN ITALY: FINAL DATA OF THE HEYMANS STUDY. (15th December 2022) - Filardi, Pasquale Perrone; Calabrò, Paolo; Galasso, Gennaro; Paloscia, Leonardo; Ignone, Gianfranco; Bridges, Ian; Dhalwani, Nafeesa; Prato, Danilo Da
Abstract: Background: Controlling lipid levels, in particular low-density lipoprotein cholesterol (LDL-C), is a proven therapeutic approach to reducing cardiovascular (CV) risk. Greater use of combination lipid-lowering therapies (LLTs) may be required to achieve the LDL-C goals recommended by the guidelines. A better understanding of the characteristics of patients receiving PCSK9is in Europe could offer the medical community an opportunity to redefine existing care pathways to better implement European guidelines, thus potentially reducing modifiable residual CV risk further. Purpose: Using data from the HEYMANS registry (NCT02770131), the objective of this analysis is to describe the Italian cohort of evolocumab patients and the long-term effectiveness and safety of the treatment. Methods: HEYMANS was a prospective registry including adults initiating evolocumab treatment in 12 European countries as part of their routine clinical management, based on local reimbursement criteria, between August 2015 and June 2020. Patient data were collected for ≤6 months before evolocumab initiation (baseline) and ≤30 months post initiation. LDL-C measurements were collected per clinical practice. At each 3-month time point in the study, we analysed median (and 95% CI) reductions in LDL-C, and the proportion of patients achieving ≥50% reductions in LDL-C from baseline. Results: Data from 311 patients from Italy were included in this final analysis (67% male, median baseline LDL-C 146 [Q1-Q3 120-177] mg/dL). Most patients (84%) were receiving evolocumab for secondary prevention, with 24% not on oral LLT, of whom the majority reported a history of statin intolerance. Within 3 months of initiating evolocumab treatment, LDL-C levels had reduced by a median of 61% and this reduction was maintained over 30 months (Figure 1). Among patients with an LDL-C value, between 66 and 76% achieved a ≥50% reduction at each visit (Figure 2). Moreover, 65% of patients receiving LLT at baseline reached an LDL-C level <55 mg/dL at any time post baseline, whilst among patients not receiving a background therapy this percentage was 48%. At the 12-month follow up, more than 97% of patients were still receiving evolocumab, with just 8 patients discontinuing the treatment (and 2 more patients leaving the study but keeping on with the treatment). That was confirmed at the 30-month follow up: almost 98% of patients still in the study beyond month 12 were receiving the drug at month 30. Moreover, at each timeframe, more than 99% had no missed dose. There were very few adverse drug reactions reported and no evolocumab-related adverse events were serious. Conclusions: In Italian clinical practice, evolocumab treatment was associated with early and sustained reductions in LDL-C, maintained over 30 months. Within 3 months of treatment, patients demonstrated a reduction in LDL-C levels greater than 60% and maintained throughout the study. These data demonstrate that meaningful, consistent additional reductions in LDL-C can be achieved with use of evolocumab. Moreover, the therapy was well tolerated by patients, with a very low discontinuation and very few missed doses.